The Effect of the QR Code Quartet Card Game on Knowledge of Fruit and Vegetable Consumption Among Adolescents - Herlina Amia; Dino Sumaryono; Ade Febryanti (Al-Hijrah Indonesia, 2026)
Background: Low consumption of fruits and vegetables among adolescents is a major concern, as it may negatively affect health and increase the risk of non-communicable diseases. Adolescents have high nutritional needs to support growth, development, and learning activities, yet many still adopt unhealthy eating habits. Engaging, technology-based educational efforts are needed to improve adolescents' knowledge about the importance of fruit and vegetable intake. Objective: To examine the effect of the QR Code quartet card game on adolescents’ knowledge of fruit and vegetable consumption at Iqra Integrated Islamic Junior High School (SMP IT Iqra), Bengkulu City. Methods: This study employed a pre-experimental one-group pretest-posttest design. A total of 33 seventh-grade students were selected using simple random sampling. The instrument used was a validated and reliable knowledge questionnaire. The intervention was carried out through a quartet card game equipped with QR Codes containing educational information on fruits and vegetables. Results: The intervention led to a significant increase in students’ knowledge. The QR Code quartet card game proved effective as an interactive learning medium that enhanced students’ understanding of the importance of fruit and vegetable consumption, while also providing an enjoyable learning experience aligned with adolescents’ familiarity with technology. Conclusion: The QR Code quartet card game can serve as an innovative and practical medium for nutrition education, applicable in schools and communities.